THE URGENCY OF THE HONOR CODE IN FORMING A CULTURE OF DISCIPLINE FOR SCOUT MEMBERS - Melida Hasibuan; Uci Kurniati; Cahaya Rani (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. Research results. Discipline of scout members in terms of language. Discipline is training memory and character in order to create supervision. or self-control or the habit of obeying provisions and orders. From this definition it can be interpreted that discipline is an awareness of doing everything in accordance with appropriate and orderly rules in accordance with applicable regulations. Discipline also has the meaning of training which makes people volunteer themselves to carry out certain patterns of behavior